Evaluation of Computer-Aided Navigation and Augmented Reality for Bicortical Mini-Implant Placement in Maxillary Expansion: An In Vitro Study - Giovanni Giovannini Riso; Javier Flores-Fraile; Gianmarco Perrone; Georgia Tzironi; Ana Belén Lobo Galindo; Cosimo Galletti; Álvaro Zubizarreta-Macho (Bioengineering)
The objective of the present study was to evaluate and compare the accuracy of the computer-aided static navigation technique (NAV), augmented reality (AR) and freehand placement technique (FHT) for the bicortical orthodontic self-drilling mini-implants for maxillary skeletal expansion (MSE) appliances placed in palate. Material and Methods: A total of 120 bicortical orthodontic self-drilling mini-implants were placed in the palate of ten 3D printed anatomically based polyurethane models of a completely edentulous upper maxilla. The orthodontic mini-implants were randomly assigned to the following placement techniques: (A) computer-aided static navigation technique (n = 40) (NAV), (B) augmented reality device (n = 40) (AR) and (C) conventional freehand technique (n = 40) (FHT). Moreover, two implants were placed in each side of the midpalatal suture in every model according to the digital planification of the expander device. Subsequently, the orthodontic mini-implants were placed and postoperative CBCT scans were performed. Finally, coronal entry-point (mm), apical end-point (mm) and angular deviations (°) were calculated using a t-test. Results: Statistically significant differences were shown at coronal entry-point (p < 0.001), apical end-point (p < 0.001) and angular deviations (p < 0.001) between the three placement techniques of bicortical orthodontic mini-implants. Additionally, statistically significant differences were also shown between the orthodontic mini-implant positions concerning the entry point (p = 0.004) and angular deviation (p = 0.004). Conclusions: The augmented reality placement technique results are more accurate, followed by the computer-aided static navigation technique and the freehand technique for MSE appliances placed in palate.